Operative Surveillance of Airway Hemangiomas in PHACE Syndrome. (February 2023) - Ramprasad, Vaibhav H.; Konanur, Anisha; McCoy, Jennifer L.; McCormick, Andrew; Jabbour, Noel; Padia, Reema
Objective: PHACE is a rare syndrome that can present with airway hemangiomas. Management for these patients is variable and the utilization of operative endoscopic airway evaluation has not been described. The objectives of this study were to identify the incidence of airway symptoms in patients being evaluated for PHACE syndrome and determine the utility of operative endoscopy. Methods: An IRB-approved retrospective cohort study was conducted on consecutive pediatric patients with head and neck infantile hemangioma (IH) evaluated in a multi-disciplinary vascular anomalies center between 2013 and 2019. Patients were included if they were being worked up for PHACE syndrome and had an otolaryngology evaluation. Demographics, clinical, and surgical variables were collected. Results: There were 317 patients with head and neck IH. Thirty-six patients met inclusion criteria. The majority of patients were female (31/36; 86.1%) and less than half of the patients (15/36; 41.7%) were eventually diagnosed with PHACE syndrome. Median age at presentation was 2 months (range 0-82 months). A total of 28/36 (77.8%) of patients were managed with propranolol. The majority of the patients presented without aerodigestive symptoms; however, 16/36 (44.4%) of patients presented with symptoms such as stridor, hoarseness, and dysphagia. A total of 20/36 (55.6%) of patients underwent operative endoscopy. A total of 8/20 (40.0%) of patients who underwent operative endoscopy had operative intervention. Of the entire cohort, only 2/15 (13.3%) patients diagnosed with PHACE were found to have a subglottic hemangioma. Both patients presented with stridor. Conclusion: Operative endoscopy remains useful in the workup of PHACE syndrome to identify subglottic hemangiomas, however there may be relatively low yield in asymptomatic patients. In office flexible laryngoscopy may be a less invasive means to examine the subglottic region. A multi-center prospective study would be necessary to evaluate incidence of subglottic hemangiomas in asymptomatic patients evaluated for PHACE.